RELATIONSHIP BETWEEN MIGRAINE AND THE OCCURANCE OF BENIGN PAROXYSMAL POSITIONAL VERTIGO (BPPV) - Eka Mahendrayana, Khairul P. Surbakti & Kiki M. Iqbal (International Journal of Research Science and Management, 2020)
Introduction: Benign Paroxysmal Positional Vertigo (BPPV) is the most common vestibular disorder. Migren also common in general population. Several studies have shown inconsistent result for the relationship between migraine and BPPV.This study aims to determine relationship between migraine and the occurance of BPPV Methode: This case control study selected subjects with consecutive sampling techniques. Sampling was conducted at H. Adam Malik General Hospital Medan and network hospital. Thirty two patients with BPPV were selected as case group and matched with thirty two patients without BPPV as control group. Migraine history was taken in medical record. This study began in March until June 2020. Result: The majority of case and control group were female with eighteen subjects (56.2%) and median age about 60.5 (27-78) years old. We found eight patients (25.0%) with history of migraine in case group and in control group four patients (12,5%) with history of migraine. There is no significance relationship in migraine and the occurance of BPPV with p= 0.33 and OR=2.33 (95% CI = 0.62-8.71) Conclusion: There is no relationship between migraine and the occurance of BPPV.